The use of radiochromic EBT2 film for the quality assurance and dosimetric verification of 3D conformal radiotherapy using Microtek ScanMaker 9800XL flatbed scanner - Sim, GS (J Appl Clin Med Phys, 2013)
Radiochromic and radiographic films are widely used for radiation dosimetry due to the advantage of high spatial resolution and two‐dimensional dose measurement. Different types of scanners, including various models of flatbed scanners, have been used as part of the dosimetry readout procedure. This paper focuses on the characterization of the EBT2 film response in combination with a Microtek ScanMaker 9800XL scanner and the subsequent use in the dosimetric verification of a 3D conformal radiotherapy treatment. The film reproducibility and scanner uniformity of the Microtek ScanMaker 9800XL was studied. A three‐field 3D conformal radiotherapy treatment was planned on an anthropomorphic phantom and EBT2 film measurements were carried out to verify the treatment. The interfilm reproducibility was found to be 0.25%. Over a period of three months, the films darkened by 1%. The scanner reproducibility was ± 2% and a nonuniformity was [Formula: see text] along the direction perpendicular to the scan direction. EBT2 measurements showed an underdose of 6.2% at high‐dose region compared to TPS predicted dose. This may be due to the inability of the treatment planning system to predict the correct dose distribution in the presence of tissue inhomogeneities and the uncertainty of the scanner reproducibility and uniformity. The use of EBT2 film in conjunction with the axial CT image of the anthropomorphic phantom allows the evaluation of the anatomical location of dose discrepancies between the EBT2 measured dose distribution and TPS predicted dose distribution. PACS number: 87.55.Qr